Innovative nanocomposite of intercalated alginate on nanomagnetite@ Al2O3@nanobentonite for uptake recovery of 152–154Eu and 60Co radionuclides from nuclear wastewater - Yasser K. Abdel-Monem; M. I. Ayad; Ayman H. Elewa; Elhassan A. Allam; Mohamed A. Gizawy; Rehab M. El-Sharkawy; Mohamed E. Mahmoud (Scientific Reports)
Abstract In this study, an innovative nanocomposite has been assembled through the intercalation of alginate onto the surface of nanomagnetite@nano-Al2O3@nanobentonite, resulting in the formation of Alg@N-Fe3O4@N-Al2O3@N-Bent. The developed nanocomposite underwent characterization through various techniques, including FT-IR, TGA, SEM, and XRD to refer to an average particle size at 80.0–90.0 nm with numerous related functional groups of its constituting unites. The evaluation of Alg@N-Fe3O4@N-Al2O3 aimed to identify its capacity to uptake and recover two radioactive nuclides, viz. 60Co and 152–154Eu, from nuclear wastewater. The outcomes of the study revealed that the most favorable conditions for the uptake of 60Co and 152–154Eu were a pH level of 6.0 and a contact time of 4.0 min. Under these conditions, the maximum uptake capacity values were determined as 82.71 mg g−1 (60Co) and 180.4 mg g− 1 (152–154Eu). The uptake process was characterized by fitting the data to pseudo-first and pseudo-second order models, in addition to this; the 152–154Eu nuclide was specifically also fitted to the intra-particle model. The related adsorption isotherm models to the uptake of 60Co and 152–154Eu were investigated and the findings indicated that 152–154Eu nuclide was well-fitted to the Langmuir and Dubinin-Radushkevich (D-R) models, whereas 60Co nuclide showed strong alignment with the Langmuir, Temkin, and D-R models. The outlined results validated the effectiveness of the Alg@N-Fe3O4@N-Al2O3 nanocomposite in the remediation of polluted nuclear wastewater with the radioactive nuclides 152–154Eu and 60Co, providing a strong emphasis in minimizing of their risks before being released into the environment.